2011
DOI: 10.1016/j.icheatmasstransfer.2011.03.021
|View full text |Cite|
|
Sign up to set email alerts
|

Natural convection flow along the vertical wavy cone in case of uniform surface heat flux where viscosity is an exponential function of temperature

Abstract: a b s t r a c tThe effect of temperature dependent viscosity μ(T), on steady two dimensional natural convection flow along a vertical wavy cone with uniform surface heat flux has been investigated. Viscosity is taken to be an exponential function of temperature. Using the appropriate variables the basic equations are transformed to non-dimensional boundary layer equations and then solved numerically employing implicit finite difference method. The effects of viscosity variation parameter on the velocity profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…The study of heat transfer with different cross-sections has gained strong interest. It is realistic to observe the patterns of fluid flow under various circumstances around surfaces of different cross-sections, such as cylinders or cones, with possible inclusions of permeability [14][15][16][17][18]. Merk and Prins [19,20] are often credited to be the pioneers in developing solutions for the fluid flow past a vertical cone considering an axisymmetric form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of heat transfer with different cross-sections has gained strong interest. It is realistic to observe the patterns of fluid flow under various circumstances around surfaces of different cross-sections, such as cylinders or cones, with possible inclusions of permeability [14][15][16][17][18]. Merk and Prins [19,20] are often credited to be the pioneers in developing solutions for the fluid flow past a vertical cone considering an axisymmetric form.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the numerical models that are valid for high Pr numbers have significantly less versatility. In terms of variable viscosity with temperature, Rahman et al [18] investigated the natural convective flow along the vertical wavy cone where viscosity was considered an exponential function of temperature. In a similar geometry, Thohura et al [30] emphasized the effects of the temperature-dependent thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Rees and Pop [16] extended by Molla et al [17] introducing complex wavy surface and they found that additional harmonic substantially changes the temperature distribution and flow field near the surface. Rahman et al [18] investigated free convection flow through a vertical wavy cone by considering temperature dependent viscosity and constant heat flux. Neagu [19] presented the analysis of the free convection flow through vertical wavy wall saturated in porous medium with heat and mass fluxes and obtained system was solved numerically.…”
Section: Introductionmentioning
confidence: 99%